Valoración de pasivos ambientales puntuales en el río Carrizal, Tosagua, Manabí por actividades antrópicas - Alcívar Loor, Gema Lisbeth (2023)
Environmental liabilities in a riverbed pose a risk to aquatic ecosystems and the communities that depend on them. The main objective of the study was to identify and evaluate the environmental liabilities associated with anthropic activities in the Carrizal riverbed, Bachillero-Puerto Larrea community. The research was divided into three phases: first, the study area was diagnosed, reconnaissance was carried out and information was collected in order to prepare thematic cartography. In the second phase, the environmental liabilities were identified and evaluated according to their importance and degree of affectation, and the water of the riverbed was also characterized to determine its quality. In the third phase, strategies for prevention and mitigation of environmental liabilities were defined for their elimination or mitigation. It was determined that the study area has geomorphologies such as coastal plains and peneplains, and diverse land uses that include areas used for agricultural and mixed activities, as well as aquaculture and livestock farming. The environmental liabilities identified in the riverbed were: domestic wastewater effluents, crops, livestock activities, and shrimp farm wastewater. The parameters analyzed that exceeded the permissible limits were turbidity and the presence of oils in the water. The environmental impacts caused in the study area are caused by anthropogenic activities have an impact on water quality, management strategies, environmentally friendly agricultural methods and strict laws are needed to protect water resources.